2021
DOI: 10.1080/19420862.2020.1868078
|View full text |Cite
|
Sign up to set email alerts
|

Innovative approaches to biologic development on the trail of CT-P13: biosimilars, value-added medicines, and biobetters

Abstract: The biosimilar concept is now well established. Clinical data accumulated pre- and post-approval have supported biosimilar uptake, in turn stimulating competition in the biologics market and increasing patient access to biologics. Following technological advances, other innovative biologics, such as “biobetters” or “value-added medicines,” are now reaching the market. These innovative biologics differ from the reference product by offering additional clinical or non-clinical benefits. We discuss these innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 96 publications
0
26
0
1
Order By: Relevance
“…Infliximab is an example of how innovation has led to treatment evolution and improvements—from the introduction of the reference product in 1998, followed by the approval of the first infliximab biosimilar (CT-P13) in 2013, and the approval of CT-P13 SC in Europe in 2019 [ 13 ]. Infliximab is the most widely studied and used anti-tumour necrosis factor (TNF) biologic for therapy of chronic immune-mediated diseases [ 23 25 ].…”
Section: The Advent Of Sc Infliximabmentioning
confidence: 99%
See 3 more Smart Citations
“…Infliximab is an example of how innovation has led to treatment evolution and improvements—from the introduction of the reference product in 1998, followed by the approval of the first infliximab biosimilar (CT-P13) in 2013, and the approval of CT-P13 SC in Europe in 2019 [ 13 ]. Infliximab is the most widely studied and used anti-tumour necrosis factor (TNF) biologic for therapy of chronic immune-mediated diseases [ 23 25 ].…”
Section: The Advent Of Sc Infliximabmentioning
confidence: 99%
“…As well as being the first infliximab biosimilar to receive regulatory approval from the European Medicines Agency (EMA) and United States (US) Food and Drug Administration (FDA) [ 13 ], CT-P13 was recognised as the first biosimilar monoclonal antibody in Japan and South Korea [ 30 , 31 ]. Global regulatory acceptance was based on the pivotal PLANETRA and PLANETAS studies in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS), respectively [ 32 , 33 ].…”
Section: The Advent Of Sc Infliximabmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether SC formulations should be defined as biobetters will need further investigations, because this area of debate is novel for both regulators and experts. 6 Nevertheless, given the reported data of equivalence an important factor in guiding treatment's choice might be patients' preference as this will ensure optimal compliance to therapy and ultimately improve patient confidence with health outcomes. 7,8 A prospective survey performed among 100 anti-tumor necrosis factor (TNF)naive patients with CD revealed that most patients preferred an anti-TNF administered by SC injection rather than by IV infusion.…”
mentioning
confidence: 99%